False claims of equivalence in the neurosurgical trauma literature: prevalence and associated factors—a systematic review protocol - Angelos G Kolias; Davi Jorge Fontoura Solla; Wellingson S Paiva; João Vitor Miranda Porto Oliveira; André Luiz Freitas Oliveira Júnior (BMJ Open)
Introduction Research quality within the neurosurgical field remains suboptimal. Therefore, many studies published in the neurosurgical literature lack enough statistical power to establish the presence or absence of clinically important differences between treatment arms. The field of neurotrauma deals with additional challenges, with fewer financial incentives and restricted resources in low-income and middle-income countries with the highest burden of neurotrauma diseases. In this systematic review, we aim to estimate the prevalence of false claims of equivalence in the neurosurgical trauma literature and identify its predictive factors.Methods and analysis The Preferred Reporting Items for Systematic Review and Meta-Analyses recommendations were followed. Randomised clinical trials that enrolled only traumatic brain injury patients and investigated any type of intervention (surgical or non-surgical) will be eligible for inclusion. The MEDLINE/PubMed database will be searched for articles in English published from January 1960 to July 2020 in 15 top-ranked journals. A false claim of equivalence will be identified by insufficient power to detect a clinically meaningful effect: for categorical outcomes, a difference of at least 25% and 50%, and for continuous outcomes, a Cohen’s d of at least 0.5 and 0.8. Using the number of patients in each treatment arm and the minimum effect sizes to be detected, the power of each study will be calculated with the assumption of a two-tailed alpha that equals 0.05. Standardised differences between the groups with and without a false claim of equivalence will be calculated, and the variables with a standardised difference equal or above 0.2 and 0.5 will be considered weakly and strongly associated with false claims of equivalence, respectively. The data analysis will be blinded to the authors and institutions of the studies.Ethics and dissemination This study will not involve primary data collection. Therefore, formal ethical approval will not be required. The final systematic review will be published in a peer-reviewed journal and presented at appropriate conferences.